The Effect of The Implementation Of Partnership and Community Development (PK and BL) and Self-Reliance of Community Partners On Community Income - Saripudin, Saripudin; Hubeis, Musa; Yusnita, Nancy (Devotion : Journal of Research and Community Service, 2022)
The focus of this research is the implementation of one of the company's PKBL, namely the Partnership and Community Development Program (PKBL) as an effort to shape the corporate image of PT. Antam, Tbk (PERSERO) Pongkor Gold Mining Business Unit, Bogor Regency. The development of this research aims to find out how the Effect of the Implementation of the PK and BL Programs and the Independence of Foster Partners on Community Income in the Nanggung District, Bogor Regency in formulating and implementing development policies in their regions, especially rural poverty alleviation programs. It is also hoped that it can be used as an academic document as reference material for small business development. The research design applies a case study pattern. From the discussion of research results, it can be concluded several things as follows: (1). There is a very real influence on the implementation of the PK and BL programs on people's income in Nanggung District, Bogor Regency. The better and more effective the implementation of PK and BL will correlate with increasing people's income with a correlation value (r) = 0.819, the coefficient of determination (r2) = 0.671, and the regression equation Y = 5.163 + 0.238X1, (2). There is a real influence of group independence in Nanggung District, Bogor Regency. It can be said that the increasing independence of the group will further increase the income.